Rancangan Protokol Kesehatan untuk Pengendalian Penyebaran Virus: Studi Kasus pada Ojek Online - Caroline Esther Suhartono; I Nyoman Sutapa (Jurnal Titra, 2021)
Occupational safety during a Covid–19 pandemic is something that needs attention related with health and physical distancing with the others. As in online transportation that can not implement physical distancing between driver and passenger. This research aim to identify hazard and risk Covid–19 virus contamination and impact to driver and passenger that using this service. Health protocols can be done in according to government and online transportation company regulation to prevent widespread transmission of the virus. Prevention that can be taken while driving by online transportation using 5 whys. The recommendations used for the most important prevention for driver and passenger from being contaminated the virus are using masks, using the personal helmet, payment methods, and spraying disinfectant on driver’s vehicles and the other surfaces.